Clinical impact of diastolic function after surgical ventricular restoration. (June 2014) - Shimamoto, Takeshi; Sakaguchi, Genichi; Komiya, Tatsuhiko
Objective: The impact of diastolic function on the clinical outcome of surgical ventricular restoration remains controversial. Methods: 71 patients undergoing surgical ventricular restoration between 1999 and 2012 were investigated. Perioperative echocardiographic parameters were compared, risk factors for deaths and cardiac events were analyzed, and actuarial freedom from death and cardiac events was computed. Results: Preoperatively, the left ventricular end-systolic volume index was 77 ± 40 mL·m −2 and left ventricular ejection fraction was 33% ± 11%. Postoperatively, left ventricular systolic function was significantly improved (end-systolic volume index 49 ± 31 mL·m −2, ejection fraction 42.1% ± 11.7%) with a 33.8% ± 21.9% reduction in left ventricular end-systolic volume index. The transmitral filling deceleration time decreased from 198 ± 54 to 150 ± 46 ms, and the ratio of early peak filling velocities increased significantly postoperatively (from 16 ± 10 to 21 ± 17). Freedom from death and cardiac events at 5 years was 78% ± 5% and 64% ± 6%, respectively. Multivariate analyses revealed that age was a significant risk factor for all-cause death, postoperative transmitral inflow pattern for cardiac death, and preoperative mitral regurgitation and postoperative transmitral inflow pattern for cardiac events. Conclusion: Despite its positive impact on systolic function, surgical ventricular restoration negatively affects postoperative diastolic function. Postoperative severe diastolic dysfunction may correlate with late mortality and cardiac events.